1982
DOI: 10.1021/ac00243a022
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of secondary amino acids with 7-nitro-4-benzofurazanyl ethers

Abstract: Five 7-nltro-4-benzofurazanyl ethers have been synthesized and their water solubilities and reactivities have been determined. 4-Methoxy-7-nltrobenzofurazan (NBD-OCH3) has a solubility similar to that of 4-chloro-7-nltrobenzofurazan (NBD-CI) but reacts ~3.5 times faster with hydroxyproline. Hydroxyproline reacts quantitatively with NBD-OCH3 In acetonltrlle-water, while considerable losses are seen when NBD-CI Is used In this medium. 4-(2-Hydroxyethoxy)-7nitrobenzofurazan Is 16 times more soluble in water than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The reaction of 2a with some amino acids was reported to yield fluorescent products 3 [48]. We decided to investigate the reaction of 2a-2f with six representative amino acids in order to study the influence of the aryl group Ar in 2.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 2a with some amino acids was reported to yield fluorescent products 3 [48]. We decided to investigate the reaction of 2a-2f with six representative amino acids in order to study the influence of the aryl group Ar in 2.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Therefore the activated 5-azit combines compactness with high sensitivity. [21] In order ido-2-nitrobenzoate derivative 20 (Scheme 5) was prepared to increase the distance to the GPI anchor structure a β-following literature procedures. [22] Reaction of 20 with 5a alanine spacer was inserted.…”
Section: Attachment Of the Labels To 5abmentioning
confidence: 99%
“…In addition, the activated chlorine atom in 4-chloro-7-nitrobenzofurazan (NBD chloride, namely NBD-Cl) can undergo electrophilic aromatic substitution by phenoxide, primary or secondary cyclic amines [10][11][12][13] and some of 4,7 di-substituted benzofurazan compounds to generate weakly or non-fluorescents products. [14][15][16][17][18] A previous kinetic study of amino-substituted NBD showed that methoxy and aryloxy substituent's are better leaving groups than chloro and that a red-colored Meisenheimer complex immediate was formed during the reactions [19].…”
Section: Introductionmentioning
confidence: 99%